Phylogenetic position, typification and emended description of Mallomonas matvienkoae (Chrysophyceae, Synurales) - Gusev, Evgeniy; Shkurina, Nataliya; Martynenko, Nikita (Phytotaxa, 2024)
We determined the phylogenetic position and clarified the morphological structure of scales and bristles of the widespread taxon Mallomonas matvienkoae Asmund & Kristiansen. The available images of M. matvienkoae scales published in floristic works from different regions of the world refer to different morphotypes. Molecular data show heterogeneity in the M. matvienkoae species complex. Therefore, a revision of this complex is required, including the establishment of the phylogenetic position and morphological type of scales and bristles of M. matvienkoae. While studying chrysophytes in Russia, we isolated and studied a strain of the genus Mallomonas. The structure of its scales is similar to the image shown in the description of M. matvienkoae. Based on material from Russia, we selected an epitype and emended the diagnosis of this taxon. Establishing the phylogenetic position and distinguishing the morphological type will help to revise numerous finds of similar morphotypes and genetic lineages previously identified as M. matvienkoae, but with obvious morphological and molecular differences from this taxon.